2021
DOI: 10.7717/peerj.10946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gut microbiota between adults with autism spectrum disorder and obese adults

Abstract: Background Autism spectrum disorder (ASD) and obesity are serious global public health problems. Studies have shown that ASD children are at a higher risk of obesity than the general population. To investigate the gut microbe characteristics of adults ASD and obese adults, we compared the gut microbiota of adults with ASD to obese adults. Methods The fecal samples were collected from 21 adult patients with ASD and 21 obese adults, and V3–V4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 73 publications
5
21
0
Order By: Relevance
“…Agathobacter and Parabacteroides were shown to be associated with metabolic disorders in humans and a murine model (Del Chierico et al, 2017;Liu et al, 2016;Salah et al, 2019;Schroeder et al, 2020). Similar to what we observed in the saliva samples, several less abundant bacterial taxa that were previously associated with obesity, including Mitsuokella and Neisseria, at the genus rank and Fusobacteriaceae and Gemellaceae, at the family rank, produced more impact on the separation of obese and lean categories than dominant bacterial taxa (Moreno-Indias et al, 2016;Palmas et al, 2021;Peters et al, 2018;Uberos et al, 2010;Zhang et al, 2021). Proportionally to all identified taxa, more organisms were significantly different in abundance between lean and obese groups in saliva samples, when compared with fecal samples, which might suggest that sampling oral microbiota may be more informative in identifying microbial biomarkers of obesity.…”
Section: Obesity Influences Microbial Community Composition Especiall...supporting
confidence: 85%
“…Agathobacter and Parabacteroides were shown to be associated with metabolic disorders in humans and a murine model (Del Chierico et al, 2017;Liu et al, 2016;Salah et al, 2019;Schroeder et al, 2020). Similar to what we observed in the saliva samples, several less abundant bacterial taxa that were previously associated with obesity, including Mitsuokella and Neisseria, at the genus rank and Fusobacteriaceae and Gemellaceae, at the family rank, produced more impact on the separation of obese and lean categories than dominant bacterial taxa (Moreno-Indias et al, 2016;Palmas et al, 2021;Peters et al, 2018;Uberos et al, 2010;Zhang et al, 2021). Proportionally to all identified taxa, more organisms were significantly different in abundance between lean and obese groups in saliva samples, when compared with fecal samples, which might suggest that sampling oral microbiota may be more informative in identifying microbial biomarkers of obesity.…”
Section: Obesity Influences Microbial Community Composition Especiall...supporting
confidence: 85%
“…Agathobacter and Parabacteroides were shown to be associated with metabolic disorders in humans and a murine model [85][86][87][88]. Similar to what we observed in the saliva samples, several less abundant bacterial taxa that were previously associated with obesity, including Mitsuokella and Neisseria, at the genus rank and Fusobacteriaceae and Gemellaceae, at the family rank, produced more impact on separation of obese and lean categories than dominant bacterial taxa [73,[89][90][91][92]. Proportionally to all identified taxa, more organisms were significantly different in abundance between lean and obese groups in saliva samples, when compared with fecal samples, which might suggest that sampling oral microbiota may be more informative in identifying microbial biomarkers of obesity.…”
Section: Obesity Influences Microbial Community Composition Especially In Salivasupporting
confidence: 81%
“…Escherichia coli and Ruminococcus gnavus were enriched in the H-VFA group and were positively correlated with metabolic indicators, the WBC, and the NEC. Additionally, studies showed that Dialister succinatiphilus was increased in obese subjects and could be used as a biomarker for predicting obesity ( Zhang et al., 2021 ). This is consistent with our results that Dialister succinatiphilus was increased in the H-VFA group.…”
Section: Discussionmentioning
confidence: 99%
“…The ECASYN-PWY, PWY0-1338, KDO-NAGLIPASYN-PWY, and PWY-6467 pathways were enriched in the H-VFA group; they were involved in the production of the lipopolysaccharide and positively correlated with the WBC and the NEC. Previous studies (Zhang et al, 2021) mentioned that lipopolysaccharide remains at low concentrations in healthy people but may reach high concentrations in obese individuals. I t l e a d s t o m e t a b o l ic e n d o t o x e m i a .…”
Section: Discussionmentioning
confidence: 99%